Genome editing for vegetable crop improvement: Challenges and future prospects - Devi, Ruma; Chauhan, Shivani; Dhillon, Tarsem Singh (Frontiers in Genetics, 2022)
Vegetable crops are known as protective foods due to their potential role in balanced human diet especially for vegetarians as they are rich source of vitamins and minerals along with dietary fibres. Many biotic and abiotic stresses threaten the crop growth, yield and quality of these crops. These crops are annual, biennial and perennial in breeding behavior. The traditional breeding strategies pose many challenges in improving the economic crop traits. As in most of the cases large number of backcrosses and stringent selection pressure is required for the introgression of the beneficial traits into the germplasm, which is quite slow and resource-intensive process. The novel breeding technique known as clustered regularly interspaced short palindromic repeats (CRISPR)-CRISPR-associated protein-9 (Cas9) has allowed the plant scientists to improve the economic traits like yield, quality, biotic stress resistance, abiotic stress tolerance and improved nutritional quality of crops more precisely and accurately. The high mutation efficiency, less off-target consequences and simplicity of this technique has made it possible to attain novel germplasm resources through gene-directed mutation. It facilitates mutagenic response even in the complicated genomes which are difficult to breed using traditional approaches. The revelation of functions of important genes with the advancement of whole-genome sequencing has facilitated the CRISPR-Cas9 editing to mutate the desired target genes. This hastens the generation of new germplasm resources required for the improvement of important agronomic traits. In this review, we will work upon this technology and its application in vegetable crops. We will cover the challenges, existing variants and the associated regulatory framework and consider future applications.